التشخيص المؤتمت للنسيج الخبيث في عينات الغدة الدرقية باستعمال تقنية التصوير الطيفي - أحمد عيسى يوسف; إبراهيم عيسى حمزة (Latakia University Journal -Medical Sciences Series, 2014)
الموت من الخباثة هو السبب الثاني في معظم بلدان العالم. يعتبر تشخيص سرطانات الغدة الدرقية من أصعب وأهم المسائل الطبية لشيوع ضخامة الغدة الدرقية، ومن المفيد استعمال طرق تشخيص تتفادى أخطاء العامل الشخصي وتعطي نتائج سريعة وأقل كلفة، مثل استعمال التصوير الطيفي المؤتمت بدل من الاعتماد بشكل كامل على المشرح المرضي. حيث يعطي التصوير الطيفي معلومات أكثر حول بنية النسيج، من خلال تكوين بصمة نسيجية تستعملها الآلة في التشخيص المؤتمت. وتم ذلك بدراسة 25 حالة سرطان درق و 26 مقطع نسيج درق غير خبيث أو طبيعي. حيث عكست نسب التشخيص الصحيح العالية في عينات السرطان (TP)= 92% و النتيجة السلبية في المقاطع غير الخبيثة(FN)=96% مصداقية هذه الطريقة في تشخيص السرطان. تمثل هذه الطريقة استعمال تقنيات الأتمتة و الذكاء الصنعي في تسهيل و تسريع تشخيص السرطانات و يمكن تعميمها على أعضاء و أنسجة أخرى. Malignancy is the second most common reason of death in most countries. Diagnosis of thyroid cancers is one of the most difficult medical problems. Therefore, it important to use diagnosing methods that bring about quick results, are less costly, and prevent errors based on personal factors. An example of such new methods is the use of automated spectral imaging, which gives more information about the structure of tissue, through the formation of fingerprint histological diagnosis used in the automated machine. This study included 25 cancer cases and 26 specimens of non-malignant thyroid or normal. The credibility of method is reflected in the high rates of correct diagnosis in cancer samples (TP) = 92% and the negative result in sections of non-malignant (FN) = 96%. This method represents the use of automation technologies and artificial intelligence to facilitate and speed up the diagnosis of cancers and can be used to diagnose other organs and other tissues.